Dependence of negative differential resistance on electronic phase separation in unpatterned manganite films - Ding, J. F. (2013)
Here, we report that small but well-defined negative differential resistance (NDR) steps can be observed at critical voltages in unpatterned millimeter-scale manganite films of Pr0.65(Ca0.75Sr0.25)0.35MnO3. We systematically investigate the magneto-transport properties of strained thin films grown on LaAlO3 and SrTiO3 substrates and map out their phase diagrams which show temperature- and magnetic-field-dependent electronic phase separation (EPS). Our data suggest that the onset of NDR only occurs “deep” within the regions of EPS, underscoring the subtle nature of filamentary transport in manganite thin films with competing phases.